2012
DOI: 10.5296/ajfa.v4i2.1990
|View full text |Cite
|
Sign up to set email alerts
|

Futures Trading and Spot Market Volatility: Evidence from Indian Commodity Markets

Abstract: In the context of emerging Indian commodity futures markets, this paper empirically examines the effect of futures trading activity (trading volume ; proxy of futures liquidity) on spot price volatility for seven agricultural commodities (guar seeds, turmeric, soya bean, black pepper, barley, Maize and Castor Seed).We decompose the futures volume into expected and unexpected components using Hodrick-Prescott filter (HP filter) .To clearly understand the destabilization effect, the relationship of the unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
3
16
1
Order By: Relevance
“…The study models volatility as conditional on time because of presence of heteroscedastic error terms (Bala & Premaratne, 2003;Booth, Martikainen, & Tse, 1997;Sehgal, Rajput, & Desting, 2013;Silvapule & Moosa, 1999;Yang et al, 2005). The error terms of asset returns show unequal variances which may be autoregressive over a period of time.…”
Section: Relationship Between Future Liquidity and Spot Volatilitymentioning
confidence: 99%
“…The study models volatility as conditional on time because of presence of heteroscedastic error terms (Bala & Premaratne, 2003;Booth, Martikainen, & Tse, 1997;Sehgal, Rajput, & Desting, 2013;Silvapule & Moosa, 1999;Yang et al, 2005). The error terms of asset returns show unequal variances which may be autoregressive over a period of time.…”
Section: Relationship Between Future Liquidity and Spot Volatilitymentioning
confidence: 99%
“…P. Srinivasan (2012) examined the price discovery process and volatility spillovers in Indian spot-futures commodity markets and the result points to dominant volatility spillovers from spot to futures market. Sehgal et al (2012) examined the futures trading activity on spot price volatility of seven agricultural commodities and found that unexpected futures trading has strong correlation on spot volatility. Chauhan et al (2013) analyzed the market efficiency of the Indian commodity market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that the price volatility in domestic markets is more than world market which designates there is no suitable price policy or trade strategy in order to manage the price volatility. To reduce the price volatility developing a well-organized spot market with transparency and efficiency should be the first goal of the government and subsequently, proper infrastructure should originate by policymakers to transfer the transactions to the parallel market (Sehgal et al, 2012). In addition, the transmission of shocks and price volatility between three markets analyzed.…”
Section: Findings and Discussionmentioning
confidence: 99%